POTENSI KOMODITAS TERNAK SAPI POTONG DAN DAYA DUKUNG LIMBAH TANAMAN PADI DI KABUPATEN SUKOHARJO - Kharisma Imam Adinata; Sunarso Sunarso; Wulan Sumekar (Universitas Tribhuwana Tunggadewi, 2016)
The aim of research were to determine 1) the main source of development of Cattle raising in Sukoharjo Regency, 2) to analyse population structure of beef cattle in Sukoharjo Regency, and 3) to analyse paddy straw as animal feed sources in Sukoharjo Regency. Method wereuse in this research was a survey method. Data analysis such as follows potential development beef cattle in Sukoharjo Regency, and cattle population structure in animal unit (AU). Secondary data were collected from official of agriculture Sukoharjo Regency, National Statistical Board, and Board of National Land, and analyse in accordance with descriptive analysis. Cattle density appertain rare with score 33,43 and 2) density of exertion farmer appertain dense with score 40,85, and 3) density of region appertain average with score 0,35. Maximum potential of land resources is 42.297,3animal unit (AU), capacity increased cattle population based on land resources is 23.230,05 animal unit, capacity increased cattle population by the head of family farmers is 14.490,75 animal unit. The value of land capability index was 1,95.